Ameliorative effects of quercetin on folliculogenesis in diabetic mice: a stereological study. (2nd October 2020) - Bolouki, Ayeh; Zal, Fatemeh; Bordbar, Hossein
Abstract: A high risk of reproductive disorders can be seen in diabetic pregnancy. Reproductive disorders associated with diabetes may result from alterations in the function of the ovary. In this study, we investigated the ameliorative effects of quercetin as a phytoestrogen and antidiabetic agent on the folliculogenesis in diabetic mice. Streptozotocin-induced diabetic mice were treated with 30 mg/kg/day quercetin for four weeks. The volume of ovary, follicles, and corpus luteum were significantly decreased in the diabetic mice. The number of growing follicles (secondary, antral, and Graafian follicles) and corpus luteum was significantly decreased in the diabetic mice. Also, the volume of oocytes was significantly decreased in antral and Graafian follicles. Our results indicated that the administration of quercetin in diabetic mice increased the volume of the ovary and growing follicles, the number of growing follicles and corpus luteum. It also significantly decreased the number of atretic follicles. As a result, it may be concluded that the impaired follicular growth and development caused by hyperglycemia in diabetic mice can be alleviated by quercetin treatment.